The Lethal Arrow Poison in the Traditional Tribal Community of Siberut Island, Indonesia - Herwig Zahorka (The Ethnobiological Society of Indonesia, 2004)
The indigenous tribal community on the island of Siberut im the Mentawar island group of Indonesia has retained an early Neolithic culture. Hunting is still performed with a bow and poison arrows. The poison is extracted from three plants: Tabernuemontana (Brvatamia) pedunculanis, Derris ellptica, and Capsicum sp. The combined poisons result in a chemical composition of bisindole alkaloids, isopropenyl-benzopyrane and benzylamid acids, as well as, most probably also, steroid glycusides. Death results mainly from cardiac and respiratory failure. The meat of the game killed with this poison is edible.